2017
DOI: 10.1002/ejic.201701355
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Size‐Dependent Trends in the Oxidation of Copper Clusters through Support Effects

Abstract: Having the ability to tune the oxidation state of Cu nanoparticles is essential for their utility as catalysts. The degree of oxidation that maximizes product yield and selectivity is known to vary, depending on the particular reaction. Using first principles calculations and XANES measurements, we show that for subnanometer sizes in the gas phase, smaller Cu clusters are more resistant to oxidation. However, this trend is reversed upon deposition on an alumina support. We are able to explain this result in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…This suggests that cluster mobility is difficult on the oxide support, in link with the experimental evidence that clusters do not sinter in the considered oxidative conditions. 34,[52][53] The GCBH approach generated a wide range of stoichiometries from Cu 4 O 2 to Though the precise agreement between such a prediction and experimental measurement is still challenging due to the approximate nature of the density functional, the impacts of clusters' structural fluxionality on the description of the phase diagram is however an intrinsic property that must be taken into account for investigating the stabilities of similar system. 57 If we consider type 1 and type 2 clusters separately, and assume that isomer equilibrium is seen only within the same type of isomers, the optimal stoichiometries of clusters of each type change with a similar trend, but the two types of Cu 4 O x clusters show different phase transition temperatures (Figure 1(c) Table S2).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that cluster mobility is difficult on the oxide support, in link with the experimental evidence that clusters do not sinter in the considered oxidative conditions. 34,[52][53] The GCBH approach generated a wide range of stoichiometries from Cu 4 O 2 to Though the precise agreement between such a prediction and experimental measurement is still challenging due to the approximate nature of the density functional, the impacts of clusters' structural fluxionality on the description of the phase diagram is however an intrinsic property that must be taken into account for investigating the stabilities of similar system. 57 If we consider type 1 and type 2 clusters separately, and assume that isomer equilibrium is seen only within the same type of isomers, the optimal stoichiometries of clusters of each type change with a similar trend, but the two types of Cu 4 O x clusters show different phase transition temperatures (Figure 1(c) Table S2).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] XANES is sensitive to geometry and to the oxidation state of the metal center, which makes it an important tool to distinguish between different structures. [9][10][11][12] The pre-edge region can be used to estimate the ligand field, spin state, and centrosymmetry of the site. [13][14][15][16][17] On the other hand, the rising-edge region can give information about geometric structure, metal-ligand overlap, ligand arrangement, and charge on the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…Tiny Cu n clusters is another example. In contrast to the gas-phase Cu n clusters, which are more difficult to oxidize the smaller they are, the supported on amorphous alumina Cu 4 were found to be oxidized easier compared to Cu 12 and Cu 20 [188]. This can be seen in the theoretically-obtained phase diagrams presented in Figure 13.…”
Section: Catalytic Applications Of Size-selected Clustersmentioning
confidence: 88%
“…This can be seen in the theoretically-obtained phase diagrams presented in Figure 13. The predictions were proven by experimentally-measured temperature at which the transition from Cu n O n/2 to Cu n occurs in a H 2 -rich environment [188]. The studies of small metal clusters and also of metal alloys have shown that expensive metals can be substituted by cheaper ones while keeping the catalytic efficiency at the same level [161,189].…”
Section: Catalytic Applications Of Size-selected Clustersmentioning
confidence: 88%
See 1 more Smart Citation